Transition to company-based vocational training in Germany by young people from a migrant background - the influence of region of origin and generation status - Beicht, Ursula [Verfasser]; Walden, Günter [Verfasser] (My University, 2019)
"For young people with a migrant background in Germany transition from school to company-based vocational training is much more difficult than for non-migrants. This remains true, when data is controlled for the lower performance of young migrants in general education. In this paper we investigate if and how far the chances of transition to company-based vocational training and the acquisition of different school leaving certificates depend from the migration generation and the region of origin of young migrants. The question is, if disadvantages of young migrants diminish with a longer stay of their family in Germany and if this is also the case for the different groups of regions of origin (Southern Europe, East Europe, Turkey, other Middle East and North Africa, Other regions). We conduct multivariate analyses on the basis of data from the German Educational Panel Study (NEPS). Our analyses relate to young people who left a general education school after Year 9 in the summer of 2011 or Year 10 in the summer of 2012. Our database comprises information provided by a total of 5,952 school leavers." (Authors' abstract, BIBB-Doku)
Keywords: P 1.1 Jugendliche; P 1.5 Migranten; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; Ausländischer Jugendlicher; Migrant; Schulabgänger; Berufseinmündung; Erste Schwelle; Einflussfaktor; Ethnische Herkunft; Schulabschluss; Multivariate Analyse; Nationales Bildungspanel